IS THE CONTROL OF CARDIOVASCULAR RISK FACTORS IS DIFFERENT IN PRIMARY AND SECONDARY PREVENTION? COMPARISON OF 2 COHORTS OF HYPERTENSIVE PATIENTS WITHIN 10 YEARS. (April 2021) - Lopez-Sublet, Marilucy; Lequeux, Benoit; Gallo, Antoine; Dourmap, Caroline; Delsart, Pascal; Coz, Sylvie Regnier Le; Steichen, Olivier; Lamirault, Guillaume; Boulestreau, Romain; Ott, Julien; Dimitrov, Yves; Sautenet, Benedicte; et al.
Abstract : Objective: Euroaspire surveys highlighted the insufficiency of control of cardiovascular risk factor (CVRF) in coronary patient in secondary prevention. Patient profiles have changed, making it difficult to analyse these data over time. Our aim was to establish the state of CVRF control in two cohorts of French hypertensive patients in different clinical situations of primary and secondary prevention by following the variables assessed in Euroaspire. Design and method: Of each of the 22 participating hypertension specialist consultations, the first 20 patients (followed for at least one year) were included. Theoretical objectives were notified for each patient according to clinical profile. Two cohorts were formed, Cohort 1 (C1) in 2009 (n = 185) and Cohort 2 (C2) in 2019 (n = 260). Patients were classified according to their prevention (P) profile: primary (P1) and secondary (P2). Results: Baseline data are summarized in Table 1. The main statistically significant results between C2 vs C1 respectively are: younger people (58.8 vs 63.9 y) and more women in P1 (50% vs 32%); higher systolic blood pressure (BP) in P2 (143.7 vs 134.7 mm Hg), whereas higher diastolic BP in P1 (81.7 vs 76.6 mm Hg); fewer diabetic patients in P1 (19% vs 41%); poorly BP targets met in P1 (43% vs 63%); lower number of antihypertensive drugs in both groups (P1: 2.17 vs 2.66; P2: 2.62 vs 3.16); prescription of statins felt by half in P1 (30% vs 43%) within 10y. Figure. No caption available. Conclusions: The high prevalence of unhealthy lifestyles, modifiable CVRF and inadequate use of drug therapies to achieve BP and lipid goals, are documented findings of the Euroaspire surveys in coronary patient, which we confirm in our hypertensive patients. Indeed, the P1 patient is less well managed than 10 years. In P2, there is no difference between the two cohorts, no improvement in BP control, possibly related with a reduction in the number of antihypertensive drugs. Ambition targets allocated for global prevention by combating the clinical inertia in titrating treatments must be a medical priority in clinical practice. Thanks to patients and Club des Jeunes Hypertensiologues.